Angiotensin II receptor blockers, steroids and radiotherapy in glioblastoma—a randomised multicentre trial (ASTER trial). An ANOCEF study. (March 2019) - Ursu, R.; Thomas, L.; Psimaras, D.; Chinot, O.; Le Rhun, E.; Ricard, D.; Charissoux, M.; Cuzzubbo, S.; Sejalon, F.; Quillien, V.; Hoang-Xuan, K.; Ducray, F.; et al.
Abstract: Background: Glioblastomas (GBMs) induce a peritumoural vasogenic oedema impairing functional status and quality of life. Steroids reduce brain tumour–related oedema but are associated with numerous side-effects. It was reported in a retrospective series that angiotensin receptor blockers might be associated with reduced peritumoural oedema. The ASTER study is a randomised, placebo-controlled trial to assess whether or not the addition of Losartan to standard of care (SOC) can reduce steroid requirement during radiotherapy (RT) in patients with newly diagnosed GBM. Patients and methods: Patients with a histologically confirmed GBM after biopsy or partial surgical resection were randomised between Losartan or placebo in addition to SOC with RT and temozolomide (TMZ). The primary objective was to investigate the steroid dosage required to control brain oedema on the last day of RT in each arm. The secondary outcomes were steroids dosage 1 month after the end of RT, assessment of cerebral oedema on magnetic resonance imaging, tolerance and survival. Results: Seventy-five patients were randomly assigned to receive Losartan (37 patients) or placebo (38 patients). No difference in the steroid dosage required to control brain oedema on the last day of RT, or one month after completion of RT, was seen between both arms. The incidence of adverse events was similar in both arms. Median overall survival was similar in both arms. Conclusions: Losartan, although well tolerated, does not reduce the steroid requirement in newly diagnosed GBM patients treated with concomitant RT and TMZ. Trial registration number NCT01805453 with ClinicalTrials.gov. Highlights: A reduced steroid requirement in patients taking angiotensin receptor blockers (ARBs) was reported in a retrospective series. This randomised trial was designed to assess if the addition of ARBs (Losartan) to standard of care can reduce steroid requirement in patients with de novo GBM. ARBs did not show any impact on steroid requirements during radiotherapy in this trial. A trend towards reduction of peritumoural oedema on magnetic resonance imaging over time was seen but did not reach statistical significance.